Effects of fructans in cryopreservation of cassava - Piranlıoğlu, Elif (My University, 2021)
Bu tezde, fruktanların manyokun kriyokoruması üzerindeki etkileri incelenmiştir. Laboratuvar ortamında çoğaltılan manyok (Bra856) türünün kriyokoruması fruktanların fiziksel ve metabolik etkileri gözlemlenerek yapıldı. Bu işlemler sırasında mikrobiyal Halomonas levan, Enzimatik Halomonas levan, HP inülin, P95 inülin, sinerji inülin ve agavin kullanıldı. İlk olarak fruktanların metabolik etkilerinin gözlemlemek için, ön-kültür besiyerinin solüsyonuna fruktanlar (% 2) ve sukroz (% 1) birlikte eklendi ve manyoktan alınan meristemler bu besiyerinin üzerine yerleştirildi. Ön-kültürleme işleminden iki hafta sonra, meristemlerin kriyoprezervasyonu gerçekleştirildi. Daha sonra, fruktanların fiziksel etkilerinin gözlemlenmesi için, manyokun kriyokoruması sırasında kullanılan bitki vitrifikasyon solüsyonuna (PVS2) fruktan (300mg / L) ve farklı dimetil sülfoksit (DMSO) yüzdeleri (% 10, 11.5 veya 13) karıştırılarak eklenmiş ve kriyokoruma gerçekleştirildi. Kriyokorumadan bir ay sonra, kriyokoruma işlemi uygulanan meristemlerin hayatta kalma oranı gözlemlendi. Her işlem en az iki kez tekrarlandı. Ayrıca metabolik ve fiziksel etkileri daha iyi olan fruktanlar ile birlikte üçüncü bir deneme yapıldı. Diğer fruktanlar arasında en iyi metabolik etkiyi gösteren P95 inülin (canlılık için kontrol % 59.5 ve kriyokoruma % 78; rejenerasyon için kontrol % 26 ve kriyokoruma % 34.5) ve diğer fruktanlar arasında en iyi fiziksel etkiyi gösteren enzimatik Halomonas levan (300 mg / L w / % 11.5 DMSO) (canlılık için kontrol % 100 ve kriyokoruma % 55.5; rejenerasyon için kontrol % 32 ve kriyokoruma % 28) olmuştur.

In this thesis, the effects of fructans on the cryopreservation of cassava were studied. This was done by observing the physical and metabolic effects that fructans could cause (Microbial Halomonas levan, Enzymatic Halomonas levan, HP inulin, P95 inulin, Synergy inulin and Agavin), on the cassava accession, Bra856, after in vitro propagation. Firstly, to observe the metabolic effects of fructans, meristems of cassava were excised and transferred onto MS medium that contains fructans (2%) and sucrose (1%). Two weeks after this preculture, the meristems were cryopreserved. Secondly, to observe the physical effects of fructans, cryopreservation of cassava was executed with PVS2 that contains fructans (300mg/ L) and different DMSO concentrations percentages (10, 11.5 or 13% (v/ v)). One month after cryopreservation, the survival rate of the cryopreserved meristems was recorded. Each experiment was repeated at least twice and in a third experiment also metabolic and physical effects of fructans were screened. P95 inulin showed the have the highest metabolic effect among all fructans (survivilty 59.5 % for control and 78% for cryopreservation; regeneration 26% for control and 34.5% for cryopreservation), and PVS2 supplemented with Enzymatic Halomonas levan (300 mg/ L w/ 11.5% DMSO) showed the result (survivililty 100% for control and 55.5% for cryopreservation; regenaration 32% for control and 28% for cryopreservation) and lastly, in order to observe both physical effect and metabolic effect of fructans they were combined and used in cryopreservation of cassava .
Keywords: Bioengineering; Biyomühendislik; cassava; Cryopreservation; Enzimatik levan; Fruktan; Halomonas Levan; inulin type fructans; inülin Fructans; kasava; kriyokoruma; levan; levan type fructans